Systematical study of reliability issues in plasma-nitrided and thermally nitrided oxides for advanced dual-gate oxide p-channel metal-oxide-semiconductor field-effect transistors - Lo, Wen-Cheng; Wu, Shien-Yang; Chang, Sun-Jay; Chiang, Mu-Chi; Lin, Chih-Yung; Chao, Tien-Sheng; Chang, Chun-Yen (My University, 2007)
In this study, we compared the effects of negative-bias temperature instability (NBTI) and hot-carrier injection (HCI) on the core and input/output (I/O) p-channel metal-oxide-semiconductor field-effect transistor (PMOSFET) fabricated using the different gate dielectrics of plasma nitrided oxide (PNO) and thermally nitrided oxide (TNO). The mobility and constant overdrive current of the PMOSFETs fabricated using PNO as a gate oxide material are about 30 and 23% higher than those of the devices fabricated using TNO, respectively. The core PMOSFETs fabricated using PNO show a better NBTI and HCI immunity than those fabricated using TNO owing to the lower nitrogen concentration at the SiO2/Si-substrate interface. However, the I/O PMOSFETs fabricated using PNO show a higher HCI-induced degradation rate because of a higher oxide bulk trap density but a better NBTI than the devices fabricated using TNO at a normal stressed bias due to a low interface trap density.
Keywords: NBTI; HCI; PNO; TNO; core; I/O